'SISTERS IN THE STRUGGLE' - Hiralal, Kalpana. ([S.l.])
1 online resource
Keywords: Sisters in the struggle': Women of Indian Origin in South Africa's Liberation Struggle 1900-1994 unveils an unchartered historical terrain, highlighting the contributions of Indian women towards non-racialism and equality and their experiences within diverse political parties; therefore, shifting the post-apartheid liberation stories which have been dominated by the journey of the ANC to other political organisations who collectively played a significant role in South Africa's road to democracy. In this book, Hiralal presents a refreshing perspective of Indians, particularly women, as contributors and activists in the struggle. The book elucidates that the struggle against apartheid was a collective endeavour among the oppressed races and not a one-sided endeavour by the ANC. The book, thus, examines the participation of Indian women against apartheid and colonialism within gendered and political frameworks.